Dampak Pembelajaran Daring Terhadap Kedisiplinan Siswa Pada Pembelajaran Agama Buddha - Tri Setya Damayanti; Hesti Sadtyadi (Jayapangus Press, 2022)
During the covid-19, social distancing is required to prevent the spread of the covid-19 virus. Therefore, in the world of education, the government applies distance education or what is often referred to as online learning. There are obstacles in online learning, such as an indication of student in discipline, which is caused by boredom with online learning, lazy to study, lack of understanding of the material being taught. This study aims to determine the impact of online learning on Buddhist students, and to determine the discipline of Buddhist students when participating in online learning. The method in this study uses a qualitative approach, namely a case study conducted at SMAN 1 Donorojo. The resultsand conclusions in this study indicate that there are positive and negative impacts arising from online learning. The positive impact is that students can recognize and operate technology well. The negative impact is that students are not able to learn independently because they do not understand if the material is not explained in detail, besides that students feel bored because of the lack of interaction with friends and teachers. Through online learning, it can be concluded that online learning makes students less disciplined, this is because students experience learning burnout due to boredom about monotonous material and the pressure from many tasks given by the teacher who are targeted to be completed on the same day. Therefore, students are lazy and bored with studying, so students are late in submitting assignments.